GE_GERICHTE C/27773/2011 vom 22. Februar 2013 - GE Cour de justice (2013)
OPPOSITION(PROCÉDURE); ORDONNANCE DE SÉQUESTRE; COMPENSATION DE CRÉANCES; EXTINCTION DE L'OBLIGATION | LP.271.1.3; LP.271.1.6; LP.80; LP.81